The Relationship Between Optimism and Academic Flow for Students of The Faculty of Psychology UNM Class Of 2020 During the Covid-19 Pandemic - Aviva R Scholten; Eva Meizara Puspita Dewi; Ahmad Yasser Mansyur (Fakulatas Dakwah IAIN Salatiga, 2022)
Abstract Academic challenges experienced by students while undergoing online lectures are expected to be a driving force to achieve flow conditions, but students perceive them as a burden that can hinder the learning process. This study aims to determine the relationship between optimism and academic flow of students of the Faculty of Psychology UNM class of 2020 during COVID-19. Using quantitative research methods. The subjects of this study were 354 students of the Faculty of Psychology UNM class 2020. The measuring instrument used in this study was the Flow Inventory for student’s scale by Yuwanto and the optimism scale by Suryaningsih. The data were analyzed using the Spearman correlation technique. The results showed that there was a positive relationship between optimism and academic flow of students of the Faculty of Psychology UNM class of 2020 (r = 0.538 and p = 0.001). This study illustrates that the higher the optimism, the higher the academic flow experienced by students.AbstrakTantangan akademik yang dialami oleh mahasiswa selama menjalani perkuliahan online diharapkan menjadi penggerak untuk mencapai kondisi flow, namun mahasiswa menganggapnya sebagai beban yang mampu menghambat proses belajar. Penelitian bertujuan untuk mengetahui hubungan antara optimisme dengan flow akademik mahasiswa Fakultas Psikologi UNM angkatan 2020 selama COVID-19. Menggunakan metode penelitian kuantitatif. Subjek penelitian ini adalah 354 orang mahasiswa Fakultas Psikologi UNM angkatan 2020. Alat ukur yang digunakan dalam penelitian ini adalah skala The Flow Inventory for student oleh Yuwanto dan skala optimisme oleh Suryaningsih. Data dianalisis dengan menggunakan teknik korelasi Spearman. Hasil penelitian menunjukkan bahwa terdapat hubungan positif antara optimisme dengan flow akademik mahasiswa Fakultas Psikologi UNM angkatan 2020 (r = 0,538 dan p = 0,001). Penelitian ini menggambarkan bahwa semakin tinggi optimisme, maka semakin tinggi flow akademik yang dialami mahasiswa.Kata kunci: flow akademik; mahasiswa; optimisme.